Numerical Simulation of Tire Reinforced Sand behind Retaining Wall Under Earthquake Excitation - Lazizi, A.; Trouzine, H.; Asroun, A.; Belabdelouhab, F. (Engineering, Technology & Applied Science Research, 2014)
This paper studies the numerical simulations of retaining walls supporting tire reinforced sand subjected to El Centro earthquake excitation using finite element analysis. For this, four cases are studied: cantilever retaining wall supporting sand under static and dynamical excitation, and cantilever retaining wall supporting waste tire reinforced sand under static and dynamical excitation. Analytical external stability analyses of the selected retaining wall show that, for all four cases, the factors of safety for base sliding and overturning are less than default minimum values. Numerical analyses show that there are no large differences between the case of wall supporting waste tire reinforced sand and the case of wall supporting sand for static loading. Under seismic excitation, the higher value of Von Mises stress for the case of retaining wall supporting waste tire reinforced sand is 3.46 times lower compared to the case of retaining wall supporting sand. The variation of horizontal displacement (U1) and vertical displacement (U2) near the retaining wall, with depth, are also presented.